Brustkrebs: Sport beschützt das Herz (Deutsche Zeitschrift für Onkologie, 2018)
Jones LW, Habel LA, Weltzien E et al. Exercise and risk of cardiovascular events in women with nonmetastatic breast cancer. J Clin Oncol 2016; 34: 2743–2749